Implementasi Bank Sampah Digital Sebagai Pendukung Ekonomi Sirkular Masyarakat Berbasis Website - Dwi Budi Srisulistiowati; Tania Fara Sayyidina; Aldiansyah Kusnadi; Daniel Dwi Kristian; Fransisco Leo Sinema Gea; Lusiana Situmorang; Lusius Reza Adiwinata; Moamar Yaseer Reza El Shihab Laurence; Muhammad Ammar Amiyoto; Muhammad Najmal Huda; Sheva Rafif Rabbani; Athala Rafi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Household waste problems continue to be a complex environmental issue due to increasing population and changes in community consumption patterns. The still conventional waste management results in low economic value of waste and an increasing burden on landfills. This community service activity aims to implement a website-based Digital Waste Bank as an effort to support the application of a circular economy and improve the effectiveness of waste management at the Pesona 015 Waste Bank Unit (BSU), RW 015, Mustika Jaya Village, Bekasi City. The implementation method is carried out participatively through stages of needs analysis, system design and development, socialization, training, assistance, and evaluation. ...Keywords— interactive media, mentimeter, merdeka belajar, online learning. The system that was developed features data recording for customers, waste deposit transactions, economic value conversion, and digital reporting. The results of the activities show that the implementation of a website-based Digital Waste Bank is able to increase the efficiency of data and transaction management by up to 85%, enhance transparency in record-keeping, and encourage active community participation in sorting and saving waste. In addition to providing economic benefits for the community, the implementation of this system also contributes to reducing the volume of waste sent to landfills and strengthens the application of the circular economy concept at the community level. Thus, a website-based Digital Waste Bank can serve as an innovative and sustainable solution for community-based waste management.